GFF Implementation Plan for the Gff Civil Society Engagment Strategy - Global Financing Facility (Global Financing Facility, 2017)
The implementation plan for the civil society engagement strategy (CSES) is developed to provide civil society organizations in countries (CSOs) with an operational framework to strengthen their engagement in the GFF process with a view to supporting the achievement of the objectives of the GFF and national investment cases. The plan reflects and builds on, and should be read in conjunction with the CSES. It is shaped and informed by GFF country implementation experiences to date, 12345 as well as the results of a targeted 2017 survey sent to CSOs working in GFF countries. The survey was geared towards understanding: 1) the civil society landscape in countries; 2) the level of knowledge of the GFF processes by CS; 3) priority actions CS can take to strengthen their engagement in the GFF processes and to support the achievement of the RMNCAH investment cases; and 4) what resources CS might need to better engage with national platforms and planning processes and to implement the identified supportive actions. The survey was sent to 18 organizations in 12 GFF countries and had a 61% response rate.
Sixth Invertors Group Meeting
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; health / saúde

Health provider responsiveness to social accountability initiatives in low- and middle-income countries: a realist review - Lodenstein, Elsbet; Dieleman, Marjolein; Gerretsen, Barend; Broerse, Jacqueline E W (Health Policy and Planning, 2017)
Social accountability in the health sector has been promoted as a strategy to improve the quality and performance of health providers in low- and middle-income countries. Whether improvements occur, however, depends on the willingness and ability of health providers to respond to societal pressure for better care. This article uses a realist approach to review cases of collective citizen action and advocacy with the aim to identify key mechanisms of provider responsiveness. Purposeful searches for cases were combined with a systematic search in four databases. To be included in the review, the initiatives needed to describe at least one outcome at the level of frontline service provision. Some 37 social accountability initiatives in 15 countries met these criteria. Using a realist approach, retroductive analysis and triangulation of methods and sources were performed to construct Context–Mechanism–Outcome configurations that explain potential pathways to provider responsiveness. The findings suggest that health provider receptivity to citizens’ demands for better health care is mediated by health providers’ perceptions of the legitimacy of citizen groups and by the extent to which citizen groups provide personal and professional support to health providers. Some citizen groups activated political or formal bureaucratic accountability channels but the effect on provider responsiveness of such strategies was more mixed. Favourable contexts for health provider responsiveness comprise socio-political contexts in which providers self-identify as activists, health system contexts in which health providers depend on citizens’ expertise and capacities, and health system contexts where providers have the self-perceived ability to change the system in which they operate. Rather than providing recipes for successful social accountability initiatives, the synthesis proposes a programme theory that can support reflections on the theories of change underpinning social accountability initiatives and interventions to improve the quality of primary health care in different settings.
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde